Overview on high potential material for Thermoelectric and their structure - Muhammad Asri, Idris; Mohd Hisyam, M.; Syamsul Bahtiar, A. G.; Rohaya, A. M.; Nur Farhana, H.; Suzilawati, A. W. (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 18th - 19th May 2005 at Putra Palace Hotel, Kangar.